2015
DOI: 10.15288/jsad.2015.76.389
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Patterns of Alcohol Mixed With Energy Drink Use Among College Students and Their Associations With Risky Drinking and Problems

Abstract: ABSTRACT. Objective:The consumption of alcohol mixed with energy drinks (AmEDs) is a form of risky drinking among college students, a population already in danger of heavy drinking and associated consequences. The goals of the current longitudinal study were to (a) identify types of AmED users between the first and second year of college and (b) examine differences among these groups in rates of highrisk drinking and consequences over time. Method: A random sample of college student drinkers (n = 1,710; 57.7% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…Heavy drinkers were 3 times more likely to consume low levels of AMED than high levels of AMED. In subsequent analyses, Mallett, Scaglione, Reavy, and Turrisi () divided student drinkers in (a) nonusers (60.4%), (b) those who initiated AMED consumption (12.4%), (c) those who discontinued AMED consumption (15.6%), and (d) continuous users of AMED (11.6%). Nonusers reported the lowest alcohol consumption and alcohol‐related consequences, whereas continuous users of AMED reported the highest rates.…”
Section: Resultsmentioning
confidence: 99%
“…Heavy drinkers were 3 times more likely to consume low levels of AMED than high levels of AMED. In subsequent analyses, Mallett, Scaglione, Reavy, and Turrisi () divided student drinkers in (a) nonusers (60.4%), (b) those who initiated AMED consumption (12.4%), (c) those who discontinued AMED consumption (15.6%), and (d) continuous users of AMED (11.6%). Nonusers reported the lowest alcohol consumption and alcohol‐related consequences, whereas continuous users of AMED reported the highest rates.…”
Section: Resultsmentioning
confidence: 99%
“…The drugs more frequently associated with alcohol use were energetic drinks, tobacco and marijuana/hashish/skunk. University students who combine alcohol use with energetic drinks consume alcohol in greater amounts and have a higher frequency of negative consequences of such use (MALLETT et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These results are comparable to recent studies, which have shown that 25 to 40% of college students have reported using AmEDs during mostly social (off campus) activities. 46,47 The higher frequency of usage of EDs among graduate students could be explained by the fact that this group has been more exposed to the possibility of consuming EDs during the completion of their undergraduate degrees.…”
Section: Consumption Of Eds and Alcoholic Beveragesmentioning
confidence: 99%